2019
DOI: 10.1088/1742-6596/1343/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Building energy flexibility: a sensitivity analysis and key performance indicator comparison

Abstract: Buildings are a key active element of the future Smart Grids with large shares of renewable energy, as they can provide flexible energy usage to help balancing power production intermittence. There is currently no consensus yet on how to quantify building energy flexibility. The various KPIs found in literature can be classified into 4 main categories: load shifting ability, power adjustment, energy efficiency and cost efficiency. Most of them use a reference scenario. Moreover, the envelope performance appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Once the application type is determined, different stakeholders should select KPIs that best suit their purposes. Recent literature has summarized building energy flexibility KPIs and demonstrated their usage [12,15,22]. Note that there are different energy flexibility modes, such as load shedding, load shifting, modulation, and onsite generation.…”
Section: Select Energy Flexibility Kpismentioning
confidence: 99%
“…Once the application type is determined, different stakeholders should select KPIs that best suit their purposes. Recent literature has summarized building energy flexibility KPIs and demonstrated their usage [12,15,22]. Note that there are different energy flexibility modes, such as load shedding, load shifting, modulation, and onsite generation.…”
Section: Select Energy Flexibility Kpismentioning
confidence: 99%
“…As mentioned above, several studies were done in regard to energy flexibility, but in general each study uses one approach only [10,18,28]. A compilation of 20 different flexibility factors for single buildings is given in [25] and in [26] 16 flexibility factors are listed for building clusters. Previous studies found focus only on one flexibility factor each or list flexibility factor values without further information about validation ranges and examples.…”
Section: Motivationmentioning
confidence: 99%
“…In general, three types of energy flexibility can be observed: (a) the temporal flexibility, (b) the amount of energy or power that can be shifted and (c) the associated cost of activating the flexibility [24]. In [25], flexibility factors are introduced which express the flexibility in regard to load-shift ability, power adjustment potential, energy efficiency and cost efficiency for single buildings. Most of the factors compare two cases: without/with load management.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…This fits into broader discussion of what flexibility is and how it emerges from socio-technical systems (Torriti & Green 2019). There is currently no consensus on how to quantify building energy flexibility (Johra et al 2019). The question for buildings is how much of that flexibility can or should be provided by this sector, and whether metrics can be developed to encourage greater flexibility.…”
Section: Timescalesmentioning
confidence: 99%